Annotated Bibliography Perpustakaan Tun Abdul Razak Issue 1/2020 - Jabatan Perancangan dan Pembangunan Perpustakaan, Bahagian Sumber Bercetak (2020)
The Annotated Bibliography Perpustakaan Tun Abdul Razak UNIVERSITI TEKNOLOGI MARA SHAH ALAM is a list of library materials added into the collection of Perpustakaan Tun Abdul Razak in Shah Alam Campus. It will be published quaterly (4 issues a year). The listed materials are available in various formats obtained through the procurement process including donation.